Investigation and improvement of load transfer efficiency of carbon nanotubes - Khor, Yeng Peng. (2013)
CNTs have long been touted as a material with immerse potential that can even be used as part of the construction of space elevators. However, many obstacles lie in the use of CNTs for macro-scale applications. Therefore, in this report, SU-8 polymer was utilized to enhance the mechanical properties, especially the load transfer efficiency of CNT fibers. A very comprehensive series of tests consisting of tensile, cyclic, step-loading and raman spectroscopy tests were carried out to attain key measurements indicative of the load transfer efficiency of the fibers, providing cross references to ensure reliability of results obtained. More importantly, it was found that SU-8 modified CNT fiber registered a G’ band raman reading downshift of 26cm-1/% strain upon tensile loading, which is comparable to that of axially aligned single-walled CNTs valued at 37.5cm-1/% strain. With the aid of the data collected, this study aims to provide a quantitative comparison of the effectiveness of SU-8 polymer infiltration on the mechanical properties of CNT fibers and act as a springboard for future CNT composite studies.